Androgen Receptor, Although Not a Specific Marker For, Is a Novel Target to Suppress Glioma Stem Cells as a Therapeutic Strategy for Glioblastoma - Zhao, Nan; Wang, Fei; Ahmed, Shaheen; Liu, Kan; Zhang, Chi; Cathcart, Sahara J.; DiMaio, Dominick J.; Punsoni, Michael; Guan, Bingjie; Zhou, Ping; Wang, Shuo; Batra, Surinder K.; et al. (Frontiers in Oncology, 2021)
Targeting androgen receptor (AR) has been shown to be promising in treating glioblastoma (GBM) in cell culture and flank implant models but the mechanisms remain unclear. AR antagonists including enzalutamide are available for treating prostate cancer patients in the clinic and can pass the blood-brain barrier, thus are potentially good candidates for GBM treatment but have not been tested in GBM orthotopically. Our current studies confirmed that in patients, a majority of GBM tumors overexpress AR in both genders. Enzalutamide inhibited the proliferation of GBM cells both in vitro and in vivo. Although confocal microscopy demonstrated that AR is expressed but not specifically in glioma cancer stem cells (CSCs) (CD133+), enzalutamide treatment significantly decreased CSC population in cultured monolayer cells and tumorspheres, suppressed tumor sphere-forming capacity of GBM cells, and downregulated CSC gene expression at mRNA and protein levels in a dose- and time-dependent manner. We have, for the first time, demonstrated that enzalutamide treatment decreased the density of CSCs in vivo and improved survival in an orthotopic GBM mouse model. We conclude that AR antagonists potently target on glioma CSCs in addition to suppressing the overall proliferation of GBM cells as a mechanism supporting their repurposing for clinical applications treating GBM.